2021
DOI: 10.1038/s41598-021-01721-5
|View full text |Cite
|
Sign up to set email alerts
|

Declining methane emissions and steady, high leakage rates observed over multiple years in a western US oil/gas production basin

Abstract: Methane, a potent greenhouse gas, is the main component of natural gas. Previous research has identified considerable methane emissions associated with oil and gas production, but estimates of emission trends have been inconsistent, in part due to limited in-situ methane observations spanning multiple years in oil/gas production regions. Here we present a unique analysis of one of the longest-running datasets of in-situ methane observations from an oil/gas production region in Utah’s Uinta Basin. The observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…The resulting trend for the Uintah Basin CH 4 enhancement for 2014-2020 is plotted in Figure 12. Lin et al (2021) show that basin natural gas production increased rapidly, peaking in 2012 and 2013, and then declined rapidly.…”
Section: Validation Of the Airs Ch 4 Enhancement Derivation Using Dat...mentioning
confidence: 99%
“…The resulting trend for the Uintah Basin CH 4 enhancement for 2014-2020 is plotted in Figure 12. Lin et al (2021) show that basin natural gas production increased rapidly, peaking in 2012 and 2013, and then declined rapidly.…”
Section: Validation Of the Airs Ch 4 Enhancement Derivation Using Dat...mentioning
confidence: 99%
“…In the contiguous United States, NO x emissions from oil and gas production contribute about 5% to the total NO x emissions, but regionally, these emissions can be a significantly larger source that affects local air quality. While methane emissions from oil and gas fields have received much recent attention, NO x and VOC emissions are more poorly described. For example, a modeling study showed that NO x emissions were overestimated by a factor of about 4, while VOC emissions were underestimated by a factor of about 2, in the regulatory emission inventory for the Uintah basin in Utah .…”
Section: Introductionmentioning
confidence: 99%
“…This is difficult because emissions from oil and gas production typically involve thousands of individual point sources, some of which may be individually large (Irakulis-Loixate et al, 2021) and others individually small but accumulating to large regional totals (Omara et al, 2022). Complicating matters is the strong and poorly understood temporal variability of emissions, both in terms of the intermittency of individual point sources (Cusworth et al, 2021a) and regional fluctuations across oil and gas production basins (Lin et al, 2021;Cusworth et al, 2022). Observations of atmospheric methane have been used extensively for top-down estimates of methane emissions through inversion of atmospheric transport models relating emissions to concentrations (Houweling et al, 2016).…”
Section: Introductionmentioning
confidence: 99%